Information on medical records of covid-19 patients in Indonesia - Wenny, Lili Sudria; Lolytasari; Putra, Riyan Adi; Merdeka, Pita; Ahwan, Muh. Ahlis; Afida, Ana (Record and Library Journal, 2024)
Background of the study: This research describes medical record management activities in two government hospitals in Indonesia, namely RSUD Tugurejo Semarang and RSUD Kota South Tangerang. This Hospital became history for the Indonesian people during the COVID-19 era and became a referral hospital for COVID-19 patients. Medical records, as written documents regarding the initial history of a patient's illness, can be trusted in the name of law and become archives with legal and historical value. Therefore, it is necessary to look at how the medical records of COVID-19 patients are recorded and utilized. Purpose: Analyze the use of COVID-19 medical records as a source of health information data in hospitals. Method: This research uses descriptive qualitative methods. Data sources come from observation, interviews, and documentation. Findings: The research results found that medical records at General Hospitals in Indonesia are managed based on life cycle files, following the guidelines issued by the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning Medical Records. Conclusion: The more organized a hospital's medical record archive is, the more information contained in the medical record will be visible to researchers.